2015
DOI: 10.1093/occmed/kqv112
|View full text |Cite
|
Sign up to set email alerts
|

Potential risk factors for haematological cancers in semiconductor workers

Abstract: The raised SIR for NHL among female workers was due to potential risk factors such as hepatitis virus infection although additional research and an ongoing, long-term, prospective epidemiological cohort study is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Interviewees in their 20s to 40s participated in the interviews, and the mean age of the interviewees was 34 years. Since more than 90% of all the employees of the company that was the background of this study were in their 20s to 40s, the age range of the interviewees was deemed suitable [24,25]. Moreover, a previous study reported significantly lower levels of commitment to healthpromoting behaviors among employees in their 30s and 40s compared to those in their 50s and 60s.…”
Section: Discussionmentioning
confidence: 97%
“…Interviewees in their 20s to 40s participated in the interviews, and the mean age of the interviewees was 34 years. Since more than 90% of all the employees of the company that was the background of this study were in their 20s to 40s, the age range of the interviewees was deemed suitable [24,25]. Moreover, a previous study reported significantly lower levels of commitment to healthpromoting behaviors among employees in their 30s and 40s compared to those in their 50s and 60s.…”
Section: Discussionmentioning
confidence: 97%
“…In previous studies of occupational LHP cancer in Korea, the study populations were limited to workers who had already applied for compensation from KCOMWEL, and analysis included approved cases only [71920]. Other studies were conducted to determine the cancer risk of workers in specific industries, and measured the exposure to hazardous materials that can cause LHP cancer [21222324]. Those studies were used to establish exposure limits and determine the causes of disease incidence.…”
Section: Discussionmentioning
confidence: 99%
“…Attributes of blood cancer used in this research were summarized following different research works (Stein & Colditz, 2004;Lee et al, 2015;Ahmed et al, 2016). The questionnaire sample is provided in a supplementary file.…”
Section: Dataset Descriptionmentioning
confidence: 99%
“…These include physical activity, food, weight control, smoking habit, pollution, and infections (Stein & Colditz 2004). Several risk factors have been identified for a variety of hematological cancers (Lee et al, 2015). Alcohol can be considered a cancer risk factor (Rehm et al, 2021).…”
Section: Introductionmentioning
confidence: 99%